QUALITY OF CHICKEN EGG RAIN PLACED ON WOOD BOX, BOXES AND EGG TRAY CARTON FOR 7 DAYS - N. R., Fransiska; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This research aims to determine the quality of eggs of chicken placed on wooden box, wire box and egg tray carton for 7 days. The research was conducted at Poultry Livestock Laboratory of Faculty of Animal Husbandry for 3 week. This research used a sample of 90 chicken eggs. The design used was Completely Randomized Design (CRD) with 6 replication and three treatments: storage using wooden box, wire box and carton egg tray at average temperature 25oC. The variables observed on egg quality test were egg weight, egg index, thick of shell, heavy of shell, yolk color, egg pH, Hought Unit egg. The result showed that storage area egg tray had significant effect (P <0,05) to the Hought Unit egg compared wooden box and wire box. While the treatment wooden box and wire box to weight of egg, egg index, thick of shell, yolk colour and pH of egg showed non significant effect (P> 0,05). From the results of this research can be concluded that chicken eggs placed on carton egg tray for 7 days can provide better quality. Keywords:   rabbit egg, storage area of wooden box, wire box, egg tray carton, egg quality, storage time